Corporate entrepreneurship in public sector: A systematic literature review and research agenda - Ivana Sučić Funko; Božidar Vlačić; Marina Dabić (Journal of Innovation & Knowledge (JIK), 2023)
After the financial crises of 2008, the contemporary public sector urged public managers, public administrators, and policymakers to consider alternatives to privatization in order to decrease government participation. This new approach to public management sought to enhance the government's performance and fulfil public needs resourcefully. The concept of corporate entrepreneurship (CE) in the public sector, i.e., public entrepreneurship (PE), was therefore introduced. This study aims to synthetize the literature on this topic and establish a research agenda on the PE field. By adapting hybrid approach based on a systematic and bibliometric literature review, the paper presents the results of four main bibliometric techniques: citation and co-citation analysis, bibliographic coupling, and co-word analysis, all of which were used by means of VosViewer software and the Bibliometrix (including Biblioshiny application) package for statistical program language R. This theme-centric review of 84 publications published in flagship journals reveals the intellectual domain of CE in the public sector, highlighting key theoretical concepts, principal research topics, the methodologies employed, the geographical span of the domain, and proposed future research avenues. This paper offers a comprehensive review of CE in the intellectual domain of the public sector. It presents fruitful research avenues with regards to the ways in which public entrepreneurial success is related to adjustability to broader political and institutional perspectives; how territorial innovation theories deal with increased resource mobility; and how a lean government could enhance civil engagement and public involvement.
Keywords: 650; Corporate entrepreneurship; Public entrepreneurship; Public sector; Systematic literature review